2011
DOI: 10.6028/nist.ir.7788
|View full text |Cite
|
Sign up to set email alerts
|

Security risk analysis of enterprise networks using probabilistic attack graphs

Abstract: The Information Technology Laboratory (ITL) at the National Institute of Standards and Technology (NIST) promotes the U.S. economy and public welfare by providing technical leadership for the nation's measurement and standards infrastructure. ITL develops tests, test methods, reference data, proof of concept implementations, and technical analysis to advance the development and productive use of information technology. ITL's responsibilities include the development of technical, physical, administrative, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 24 publications
0
37
0
2
Order By: Relevance
“…Wang et al [42] suggested an overall network security score by combining individuals' vulnerabilities regarding their relationship in attack graphs. Singhal et al [38] defined the risk score as the likelihood of an attack which was derived from the likelihood of individual exploits. Noel et al [26] described four families of metrics for measuring security risk in attacks graph.…”
Section: Attack Graph Optimizationmentioning
confidence: 99%
“…Wang et al [42] suggested an overall network security score by combining individuals' vulnerabilities regarding their relationship in attack graphs. Singhal et al [38] defined the risk score as the likelihood of an attack which was derived from the likelihood of individual exploits. Noel et al [26] described four families of metrics for measuring security risk in attacks graph.…”
Section: Attack Graph Optimizationmentioning
confidence: 99%
“…However, most of the attack graph models only show all possible attack paths to the administrator, and they could not tell the administrator which is most likely path to be used by the attacker for some given conditions. Some researches tried to append probabilities on the attack graph, such as [15]- [17], but some of them estimated the probabilities by their individual experiences. For instance, the scheme of [17] has applied the well-known CVSS to set up the initial probabilities; however, they only took one metric, Access Complexity, into consideration.…”
Section: Attack Strategy Prediction With Precisely Estimated Probabilmentioning
confidence: 99%
“…Some researches tried to append probabilities on the attack graph, such as [15]- [17], but some of them estimated the probabilities by their individual experiences. For instance, the scheme of [17] has applied the well-known CVSS to set up the initial probabilities; however, they only took one metric, Access Complexity, into consideration. We think the result is inaccurate since the other two metrics, Access Vector and Authentication, are also major factors for successfully exploiting the vulnerability.…”
Section: Attack Strategy Prediction With Precisely Estimated Probabilmentioning
confidence: 99%
“…Throughout this work, we will illustrate the steps and concepts using a running example borrowed from [38]. This reference describes a simple version of TVA (see, e.g., [31]) and attack graph modeling, based on a small infrastructure that is shown in Fig 1: The system consists of three machines (numbered as 0, 1 and 2), with several services being open on each node (such as file transfer protocol (FTP), remote shell (RSH) and secure shell (SSH)).…”
Section: A Running Examplementioning
confidence: 99%